2019
DOI: 10.30699/jambs.27.123.31
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Intravenous Lidocaine Infusion in Cesarean Section under Spinal Anesthesia: A Prospective Randomized Double-Blind Study

Abstract: 10.30699/jambs.27.123.23 Background & Objective: Nowadays, conventional analgesic agents that are usually used for pain killing after cesarean sections do not provide enough analgesia with infrequent serious side effects. Lidocaine has been suggested as an adjuvant analgesic agent for postoperative pain relief. We designed this randomized doubleblind, placebo-controlled study to evaluate the analgesic efficacy of intravenous lidocaine in patients undergoing a cesarean section under spinal anesthesia. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…In the present study, patients in the placebo group and the melatonin group received more opioid analgesia at a dose of 5 mg. Similarly, in the study of Khezri et al [ 34 ], patients receiving melatonin at a dose of 6 mg received more analgesia than patients receiving melatonin at a dose of 3 mg. On the other hand, studies have shown that the incidence of side effects of prescribed exogenous melatonin, even at high intravenous doses, is very rare [ 39 , 40 ]. A review reported long-term side effects of melatonin like dizziness, drowsiness and somnolence in patients undergoing general anesthesia surgery [ 41 ] and cognitive decline in elderly patients under general anesthesia in hip surgery [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the present study, patients in the placebo group and the melatonin group received more opioid analgesia at a dose of 5 mg. Similarly, in the study of Khezri et al [ 34 ], patients receiving melatonin at a dose of 6 mg received more analgesia than patients receiving melatonin at a dose of 3 mg. On the other hand, studies have shown that the incidence of side effects of prescribed exogenous melatonin, even at high intravenous doses, is very rare [ 39 , 40 ]. A review reported long-term side effects of melatonin like dizziness, drowsiness and somnolence in patients undergoing general anesthesia surgery [ 41 ] and cognitive decline in elderly patients under general anesthesia in hip surgery [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 83%
“…In the study of Khezri et al [ 34 ], the incidence of complications was almost the same in the three groups, and only in the group receiving 6 mg melatonin, the incidence of headache was significantly higher than the other two groups. However, in the present study, no side effects were observed in patients receiving 10 mg melatonin at a dose of 10 mg, while in patients receiving placebo and 5 mg melatonin were presented with headache and nausea/vomiting.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There were no significant differences between the three groups in terms of side effects, either intraoperatively or postoperatively, including pruritus, nausea/vomiting, vertigo, dizziness, and respiratory depression. 24 Some researchers have reported that premedication by oral melatonin 3 or 5 mg can reduce the need for propofol for induction and not increase the post-anesthesia recovery stay period. 25 Limitations to our study include the small sample size involved.…”
Section: Discussionmentioning
confidence: 99%
“…Since literature on the effects of intraoperative infusion of lignocaine during spinal anaesthesia on the BIS was limited, we chose a dose of lignocaine with the acceptable efficacy and the least toxicity for mother and the fetus. [ 7 12 20 21 ]…”
Section: Discussionmentioning
confidence: 99%